Numbers scepticism, equal chances and pluralism: Taurek revisited. (August 2016) - Lang, Gerald; Lawlor, Rob
The 'standard interpretation' of John Taurek's argument in 'Should the Numbers Count?' imputes two theses to him: first, 'numbers scepticism', or scepticism about the moral force of an appeal to the mere number of individuals saved in conflict cases; and second, the 'equal greatest chances' principle of rescue, which requires that every individual has an equal chance of being rescued. The standard interpretation is criticized here on a number of grounds. First, whilst Taurek clearly believes that equal chances are all-important, he actually argues for a position weaker than the equal greatest chances principle. Second, the argument Taurek gives for the importance of equal chances ought to commit him to being more hospitable to the significance of numbers than he seems to be. Third, and as a result, Taurek should not have dismissed the significance of numbers but embraced a form of pluralism instead. Fourth, this result should be welcomed, because pluralism is more plausible than either the equal greatest chances principle or the saving the greater number principle.